Determination of Global Mean Eddy Diffusive Transport in the Mesosphere and Lower Thermosphere From Atomic Oxygen and Carbon Dioxide Climatologies. Issue 23 (5th December 2019) - Swenson, G. R.; Salinas, C. C. J. H.; Vargas, F.; Zhu, Y.; Kaufmann, M.; Jones, M.; Drob, D. P.; Liu, A.; Yue, J.; Yee, J. H.
Abstract: Quantifying the eddy diffusion coefficient profile in the mesosphere and lower thermosphere (MLT) is critical to the constituent density distributions in the upper mesosphere and thermosphere. Previous work by Swenson et al. (2018, https://doi.org/10.1016/j.jastp.2018.05.014 ) estimated the global mean eddy diffusion ( k z z ) values in the upper mesosphere using atomic oxygen (O), derived from Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) hydroxyl (OH). In this study, vertical eddy diffusive transport velocities of O were determined from continuity of mass in the mesopause region (80–97 km), primarily via the HO x chemistry. Global average constituent climatology from previously deduced SABER ozone (O3 ) and atomic hydrogen (H) was applied. Furthermore, we extended the global mean eddy transport velocities to new heights (105 km) in the MLT using the newly available global mean Scanning Imaging Absorption Spectrometer for Atmospheric Chartography (SCIAMACHY) data. The combined method of determining O3 loss and O density climatology from SCIAMACHY, as well as an improved global mean background atmosphere from SABER, provides new information for eddy diffusion determination in the MLT. Three prominent results to emerge from this study include (i) global mean k z z profiles between 80 and 105 km derived from MLT constituent climatologies, SABER, and SCIAMACHY global mean O density profiles averaged for approximately one solar cycle, (ii) determination of O eddy diffusion velocities in the MLT consistent between two satellite measurements and the thermosphere‐ionosphere‐mesosphere‐electrodynamics general circulation model, and (iii) resolution of historically large differences between deduced k z z determined from O versus CO2 by analysis of SABER and SCIAMACHY measurements. Key Points: Global mean vertical transport velocities of atomic oxygen in the MLT (80–105 km) were determined from SABER and SCIAMACHY The resolution of historical differences in the eddy diffusion coefficients between O and CO2 have been resolved (above 85 km) The values of eddy diffusion coefficients increase above 85 km to a maximum above 100 km, where little information has been available